The therapeutic potential of kukoamine A from Lycii Radicis Cortex in Caenorhabditis elegans for sarcopenia treatment - Lee, Sohyun; Youn, Esther; Nguyen, Tran Tu Uyen; Kim, Chul Young; Kang, Kyungsu (KSABC International Symposium 2024, 2024)
Sarcopenia, an age-associated syndrome, is marked by the deterioration of muscle mass and strength, with no currently effective pharmacological treatments available. Kukoamine A (KA), a principal constituent of Lycii Radicis Cortex(LRC), was investigated for its effects on muscle health using Caenorhabditis elegans as a model organism. In this study, mild heat (25℃) was applied to C. elegans to induce accelerated aging and muscle decline, thereby shortening the experimental duration needed to evaluate the protective effects of KA. The swimming activity of C. elegans decreased after four days of mild heat treatment, but treatment with 100 μM KA was able to counteract this movement defect. Muscle mitochondrial morphology was assessed via imaging the area opposite the vulva. The KA-treated group exhibited significantly better preservation of muscle mitochondrial structure. In addition, KA treatment activates the unfolded protein response of the ER (UPRER) in C. elegans, as shown by significantly elevated hsp-4p::GFP expression levels compared to control. These findings indicate that KA exerts beneficial effects on muscle health, suggesting its potential as a therapeutic agent for sarcopenia.